A STUDY ON FACTORS INFLUENCING STRESS OF EMPLOYEES OF A BANK IN MALAYSIA - et. al, Dr Razali Shahul Hameed (International Journal of Advanced Science and Technology, 2020)
The purpose of this study is to investigate stress factors towards employees in a bank. Statistical Package of the Social Science was utilized as the main statistical tool for data analyzing. Stress represents independent variable, whereas, organizational, personal, and working environment factor represent three dependent variables. Questionnaires administered among 99 employees who worked in a bank. Regarding the findings, there are significant impacts of organizational factors, personal factors and working environment factors on stress for those employees who worked in that bank. In a nutshell, working environment factor is the most significant factor toward stress, followed by personal factors and then the organizational factors.